Cookery 10 : technology and livelihood education : modules in home economics - Peralta, Joana C. (Quezon City : St. Bernadette Publishing House Corporation, 2015)
"This book is compilation of all the necessary lessons that will give an opportunity for developing and enhancing the skills that are needed in cooking". the module start's with the discussion of the Personal Entrepreneurial Competencies that cook should possess, as well as the ability to explore for business opportunity. the four units deal with the most important aspects of cooking and the different method preparation that will help a would be entrepreneur start a simple business. this will give them a hands on activities on the actual preparation of cooking of different kinds of food including the choice of ingredients, together with preparation, cooking, plating or presentation, serving, and packaging of some foods".
English text.
Keywords: Cooking